Yigael Yadin to Head New Excavation (The Biblical archaeology review, 1978)
Signaling an eventual return to the world of archaeology, Yigael Yadin has stated he will lead a major new archaeological excavation. Yadin, formerly head of Hebrew University’s Institute of Archaeology, is currently Israel’s Deputy Prime Minister.